Quality risk management of top spray fluidized bed process for antihypertensive drug formulation with control strategy engendered by Box‑behnken experimental design space - Mukharya, Amit; U Patel, Paresh; Shenoy, Dinesh; Chaudhary, Shivang (International Journal of Pharmaceutical Investigation, 2013)
Introduction: Lacidipine (LCDP) is a very low soluble and highly biovariable calcium channel blocker used in the treatment of hypertension. To increase its apparent solubility and to reduce its biovariability, solid dispersion fluid bed processing technology was explored, as it produces highly dispersible granules with a characteristic porous structure that enhances dispersibility, wettability, blend uniformity (by dissolving and spraying a solution of actives), flow ability and compressibility of granules for tableting and reducing variability by uniform drug‑binder solution distribution on carrier molecules. Materials and Methods: Main object of this quality risk management (QRM) study is to provide a sophisticated “robust and rugged” Fluidized Bed Process (FBP) for the preparation of LCDP tablets with desired quality (stability) and performance (dissolution) by quality by design (QbD) concept. Results and Conclusion: This study is principally focusing on thorough mechanistic understanding of the FBP by which it is developed and scaled up with a knowledge of the critical risks involved in manufacturing process analyzed by risk assessment tools like: Qualitative Initial Risk‑based Matrix Analysis (IRMA) and Quantitative Failure Mode Effective Analysis (FMEA) to identify and rank parameters with potential to have an impact on In Process/Finished Product Critical Quality Attributes (IP/FP CQAs). These Critical Process Parameters (CPPs) were further refined by DoE and MVDA to develop design space with Real Time Release Testing (RTRT) that leads to implementation of a control strategy to achieve consistent finished product quality at lab scale itself to prevent possible product failure at larger manufacturing scale.
Keywords: Critical process parameter; critical quality attribute; failure mode effective analysis; fluidized bed process; quality by design; quality risk management; scale-up